KEMAMPUAN LITERASI DIGITAL DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA SMA - Vania Anarizka; Jaja Wilsa (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this research is to explain the digital literacy abilities of high school students in learning Indonesian. The research method used is descriptive qualitative with an analytical descriptive approach. This research will find out how high the digital literacy skills of SMAN 1 Astanajapura students are in learning Indonesian which refers to the four digital literacy competency competencies, namely information dissemination on the internet (Internet Searching); hypertextual navigation; evaluation of information content (Content Evaluation); preparation of knowledge (Knowledge Assembly). The sample of this research was 30 students of class X SMAN 1 Astanajapura. The instrument used is a questionnaire via google form. The results of this study indicate that class X students of SMAN 1 Astanajapura have mastered the four digital literacy competencies which are categorized as good in learning Indonesian.